Biosimilars in Dermatology: Analytical, Regulatory, and Clinical Considerations: A Treatise From the Medical Board of the National Psoriasis Foundation. Issue 3 (July 2019) - Yamauchi, Paul S.; Sachsman, Suzanne M.; Wu, Jashin J.; Siegel, Michael; Van Voorhees, Abby; Armstrong, April; Kay, Jonathan
Despite the recent approvals of biosimilars in the United States, the current landscape is still an evolving process. The overall impetus for the passage of the Biologics Price and Competition Act of 2009 and the abbreviated pathway for the development of biosimilars are to decrease the economic burden of biologics and increase access to qualified patients. The regulatory agenda for biosimilars involves an analytical approach through methods embodying a "totality of evidence" to demonstrate that a biosimilar has no clinically meaningful differences compared to the reference product. The establishment of extrapolation and interchangeability in a developmental program for biologics has no precedence for implementation. Because of these unique parameters associated with biosimilars, further mitigation is necessary to address concerns among health-care professionals. The acceptance and utilization of biosimilars in the United States may gain traction similar to generic drugs if reduced costs, increased access, and alleviation of concerns from clinicians are attained.